Fluid and metal sources in the Fäboliden hypozonal orogenic gold deposit, Sweden - Bark, Glenn; Boyce, Adrian J.; Fallick, Anthony E.; Weihed, Pär (Mineralium Deposita, 2021)
To model the formation of orogenic gold deposits, in a global perspective, it is important to understand the ore-forming conditions not only for deposits hosted in greenschist facies rocks but also in amphibolite facies. The Paleoproterozoic Fäboliden deposit in northern Sweden belongs to the globally rare hypozonal group of orogenic gold deposits and, as such, constitutes a key addition to the understanding of amphibolite facies orogenic gold deposits. The Fäboliden deposit is characterized by auriferous arsenopyrite-rich quartz veins, hosted by amphibolite facies supracrustal rocks and controlled by a roughly N-striking shear zone. Gold is closely associated with arsenopyrite-löllingite and stibnite, and commonly found in fractures and as inclusions in the arsenopyrite-löllingite grains. The timing of mineralization is estimated from geothermometric data and field relations at c. 1.8 Ga. In order to constrain the origin of gold-bearing fluids in the Fäboliden deposit, oxygen, hydrogen, and sulfur isotope studies were undertaken. δ18O from quartz in veins shows a narrow range of + 10.6 to + 13.1‰. δD from biotite ranges between − 120 and − 67‰, with most data between − 95 and − 67‰. δ34S in arsenopyrite and pyrrhotite ranges from − 0.9 and + 3.6‰ and from − 1.5 and + 1.9‰, respectively. These stable isotope data, interpreted in the context of the regional and local geology and the estimated timing of mineralization, suggest that the sulfur- and gold-bearing fluid was generated from deep-crustal sedimentary rocks during decompressional uplift, late in the orogenic evolution of the area. At the site of gold ore formation, an 18O-enriched magmatic fluid possibly interacted with the auriferous fluid, causing precipitation of Au and the formation of the Fäboliden hypozonal orogenic gold deposit.